Aspects of Criminal Sanctions in Corruption from Islamic Legal Perspectives (FUQAHA) And Law in Indonesia - Dedi; Rusydi , Ibnu (Contemporary Journal of Applied Sciences, 2024)
The purpose of this study was to ascertain Imam Madzhab's perspectives on corruption and the underlying assumptions that underlie each perspective. Normative legal research was the research methodology employed in this study. When viewed within the larger framework of Islamic teachings, corrupt practices are defined as behaviors that run counter to the values of responsibility, justice, and accountability. Damage to the earth (facade) can be categorized as one of the many distortions brought about by corruption in the state and society. Imam Madzhab's views on punishing corrupt individuals are predicated on classifying corruption as a Jarimah Takzir. If an act of violating human rights or the rights of Allah is committed and these violations are not specifically stated in the Quran and Hadiths as sanctions, then takzir is a legal sanction that is imposed on the offender of Jarimah or a criminal act that falls under the jurisdiction of judges or rulers. Takzir may face jail time, fines, being added to a list of repugnant people, laws prohibiting termination, or even the death penalty as legal penalties.